The Quest for Non-Resource-Based FDI : Do Taxes Matter? - Kinda, Tidiane (IMF Working Papers; Working Paper, 2014)
Using manufacturing and services firm-level data for 30 sub-Saharan African (SSA) countries, this paper shows that taxation is not a significant driver for the location of foreign firms in SSA, while other investment climate factors, such as infrastructure, human capital, and insitutions, are. By analyzing disaggregate FDI data, the paper establishes that, while there is considerable contrast in behavior between vertical FDI (foreign firms producing for export) and horizontal FDI (foreign firms producing for local markets), taxation is not a key determinant for either type of FDI. Horizontal FDI is attracted to areas with higher trade regulations, highlighting interest in protected markets. Furthermore, horizontal FDI is affected more by financing and human capital constraints, and less by infrastructure and institutional constraints, than is vertical FDI.